A numerical and experimental investigation on microscale heat transfer effect in the combined entry region in macro geometries - Kong, Kian Shing (2013)
The rising heat dissipation problem in electronic devices has led to numerous investigations on microchannel heat sink. However, literature shows that microscale heat transfer is generally not being applied to macro geometries, which is believed largely due to the fabrication and operational challenges. In the present study, experiments were conducted in a conventionally-sized circular channel which was manufactured through conventional techniques. The channel has a nominal diameter of 20 mm and length of 30 mm. An insert was placed concentrically into the channel to make the flow path small enough to behave like a microchannel in order to attain high heat removal capabilities. Under such a construction, various sizes of channel can be formed by placing different sizes of insert, one at a time, into the circular channel. The experiments and numerical simulations were conducted for nominal gap sizes of 1000 and 300 μm over a range of Reynolds numbers from 1000 to 5500 and heat fluxes from 5.3 to 37.1 W/cm2 in the combined entry region. The experimental findings showed that the design was able to achieve a maximum heat transfer coefficient of 68 kW/m2 K with single-phase water flowing through the annular channel of gap size of 300 μm at Reynolds number of 5200. Comparisons of measurements from the 300-μm case with the numerical solutions showed good agreement for pressure drop predictions with an average deviation of 4.5% but poor agreement for the Nusselt number predictions with deviation of more than 30% for cases at higher Reynolds number. Most importantly, the experiments have demonstrated the possibility of achieving microscale heat transfer effects in macro geometries using readily available conventional fabrication methods. With microscale heat transfer effects easily available, it also presents an opportunity to effectively improve the heat removal capabilities of a macroscale heat exchanger in the near future.